AB0373 Analysis of risk factor for locomotive syndrome in patients with rheumatoid arthritis: data from chikara study. (15th June 2017) - Yamada, Y; Tada, M; Mandai, K; Hidaka, N
Abstract : Background: Patients with rheumatoid arthritis (RA) are at a higher risk for sarcopenia due to joint destruction and chronic inflammation*1, which can lead to locomotive syndrome (LS), i.e., being restricted in the ability to walk or lead a normal life owing to a dysfunction in one or more of the parts of the musculoskeletal system*2. The prospective observational CHIKARA study (Correlation research of sarcopenia, skeletal muscle and disease activity in rheumatoid arthritis; registration number UMIN000023744) was begun in 2016 to investigate the correlation between RA disease activity and sarcopenia and LS. Objectives: We investigated the relationship between LS and disease activity at baseline in patients with RA. Methods: One hundred patients (78% women; average age, 66y) enrolled in the CHIKARA study were examined for body weight, muscle mass, fat mass, predicted bone mass, basal metabolic rate (BMR), leg muscle score, etc., using a body composition analyzer. Laboratory data, disease activity, Health Assessment Questionnaire (HAQ) and treatment were also investigated. LS was diagnosed using a questionnaire called Locomo-5. We investigated the correlation between LS and each status using univariate and multivariate analyses. Results: Fifty-two percent of the patients with RA that we examined had LS. Mean disease duration was 5.5 years and mean DAS28-ESR was 3.55. Table 1 shows the risk factors for LS. Univariate analysis showed that age, percent body fat, body weight, visceral fat rating, leg muscles score, rheumatoid factor status and HAQ had significant associations to LS. Leg muscle score and HAQ were detected as significant factors by multivariate analysis. Patients whose leg muscle score was less than 90 had a significantly higher prevalence of LS by ROC curve analysis (Odds ratio 3.77, p=0.001). Disease activity and use of glucocorticoids or biological agents showed no significant relationship. Conclusions: Lower leg muscle score and higher HAQ score are independent risk factors for LS among patients with RA. References: Inui K., Koike T., Tada M., et al. Sarcopenia is apparent in patients with rheumatoid arthritis, especially those with biologics -TOMORROW study-. EULAR 2015 abstract (AB0359). Nakamura K., Ogata T. Locomotive Syndrome: Definition and Management. Clin Rev Bone Miner Metab. 2016; 14(2): 56–67. Disclosure of Interest: None declared